2020
DOI: 10.3390/ma13020345
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Corrosion Behavior in Marine Environment of MAO Coatings on Magnesium Alloy

Abstract: To improve the corrosion performance of magnesium alloys in the marine environment, the MAO, MAO–Cu2CO3(OH)2·H2O and MAO–Cu2P2O7 ceramic coatings were deposited on AZ91D magnesium alloys in basic electrolyte and the discoloration mechanism of the Cu-doped MAO coatings and the corrosion behavior of the three MAO coatings in the artificial seawater solution were investigated by SEM, EDS and XPS. The results indicated that the formation and discoloration mechanism of the brown MAO ceramic coatings were attributab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…When a capacitor is omitted from the circuit, no current can flow because, when the capacitor is charged, the current will not pass, and the circuit will be cut off. The dense oxide layer on the surface of the titanium also has this effect and, such as a capacitor after being fully charge, disrupts the electrical circuit by reducing the corrosion rate [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Based on the EIS diagrams and the obtained data, it can be concluded that the corrosion resistance of the sample with plasma electrolytic oxidation coating is better than that of the uncoated sample.…”
Section: Resultsmentioning
confidence: 99%
“…When a capacitor is omitted from the circuit, no current can flow because, when the capacitor is charged, the current will not pass, and the circuit will be cut off. The dense oxide layer on the surface of the titanium also has this effect and, such as a capacitor after being fully charge, disrupts the electrical circuit by reducing the corrosion rate [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Based on the EIS diagrams and the obtained data, it can be concluded that the corrosion resistance of the sample with plasma electrolytic oxidation coating is better than that of the uncoated sample.…”
Section: Resultsmentioning
confidence: 99%
“…This can also be proved in Lee’s research [ 32 ], which clarified that the incorporation of ZrO 2 can improved corrosion property of MAO coatings effectively. It should be noted that there exist lots of MgF 2 concentrated in the micropores, according to Liu’s research [ 33 ], the deterioration rate of the MAO coating compounds can be reduced by the presence of MgF 2 when MAO coating was exposed to corrosive medium, so the existence of MgF 2 is of great help in preventing corrosive ions from reaching substrate surface quickly [ 34 ]. In addition, this is also the result of compacter structures and thicker coatings working together.…”
Section: Resultsmentioning
confidence: 99%
“…With the development of science and technology, aluminum alloys have been developed rapidly, especially in the application of marine construction [1][2]. Aluminum alloys are light in weight and possess many outstanding mechanical properties.…”
Section: Introductionmentioning
confidence: 99%